TERAPI SENI SEBAGAI CARA UNTUK MENINGKATKAN EMOSI POSITIF ORANG LANJUT USIA YANG TINGGAL DI PANTI LANSIA - Ajisuksmo, Clara R.P.; Puspasari, Anita; Erianti, Dela; Maharani Dewanti , Dhea; Parera , Raul Julio; Gunawan , Angelina; Sabbathya , Sandrina; Widayanti, Anindha; Sugito , Irene Betzy; Rosario , Teressa M.; Soge , Yeremias S.I. (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to increase the positive emotions of the elderly living in elderly homes. Previous studies have reported that changes in the physical, psychological, cognitive, and social functions of the elderly affect their mental health. Elderly experience stress, anxiety, and depression due to the changes that occur to them. Therefore, the elderly should live with their families since they need support from the family members. However, there are elderly people who are entrusted by their families to elderly homes. The elderly who live with their families have more positive emotions and meaning of life than those who live in elderly homes. This community service activity is aimed at improving positive emotions of the elderly who live in elderly homes. It was carried out at the elderly home in North Jakarta, and implemented an art therapy method where the elderly were invited to paint glass jars with acrylic paint or draw on paper using the thread pulling technique. Overall, there were 28 elderly participated (8 men and 20 women) in this activity. After finishing painting and drawing with acrylic paint, students of Faculty of Psychology sit together with the elderly to talk and listen to the elderly’s feelings.